Health Education with A Peer Group Support Approach in Increasing Knowledge About Booster Vaccination in Farmers: Pendidikan Kesehatan Dengan Pendekatan Peer Group Support Dalam Peningkatan Pengetahuan Tentang Vaksinasi Booster Pada Petani (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
Working as a farmer requires you to know how to prevent work accidents from occurring when working in the rice fields. Using personal protective equipment and having a healthy lifestyle is very important and must be maintained to decrease morbidity rates. In the COVID-19 pandemic conditions, special attention is also required so that the risk of contracting the virus can be maximally reduced. COVID-19-positive patients do not choose people and places; anyone who does not have a healthy lifestyle and is not in prime body condition could be infected with this virus, including in the Kalisat-Jember District. Handling this pandemic has been a process for the last few months and years, but public compliance still needs improvement, especially in public facilities. Even though there is no cure for COVID-19, transmission of this virus can be prevented, one of which is with the government's vaccination program. This program is currently in its second booster stage. The hope is that the wider community can and will be able to adapt to the Covid-19 virus. Therefore, health education aims to use a peer group approach to help people understand the benefits of booster vaccines.